AB0001 Genotype and Haplotype Effects of 7 Single-Nucleotide Polymorphisms in the CRP Gene on Levels of C-Reactive Protein and DAS28 in Two Cohorts of Treatment NaÏVe, Recent Onset Rheumatoid Arthritis Patients. (10th June 2014) - Ammitzbøll, C.G.; Steffensen, R.; Bøgsted, M.; Hørslev-Petersen, K.; Hetland, M.L.; Junker, P.; Pødenphant, J.; Østergaard, M.; Ellingsen, T.; Johansen, J.; Stengaard-Pedersen, K.
Abstract : Background: Single nucleotide polymorphisms (SNPs) in the C-reactive protein ( CRP) gene are implicated in the regulation of the constitutional CRP expression and its response to pro-inflammatory stimuli. Previous reports suggest that these effects may influence instruments for clinical decision-making based on CRP, e.g. DAS28. Objectives: To investigate the associations between 7 CRP SNPs, their haplotypes, the serum level of CRP and DAS28 in recent onset, treatment naïve RA (rheumatoid arthritis) patients. Methods: 315 DMARD and steroid naïve RA patients with disease duration <6 months were included from two randomized controlled trials (CIMESTRA (n=135), OPERA (n=180)). The genotype and haplotype associations to CRP and DAS28 at baseline and after one year of active treatment were evaluated using linear regression analysis adjusted for age, sex and treatment. Genotyping were analyzed by the TaqMan OpenArray system. The results from the combined cohorts are presented. Results: The minor allele of rs1205 C>T was associated with decreased CRP levels at baseline (p=0.03). The TT genotype showed a 50% reduction in CRP from 16.7 to 8.4 mg/l (p=0.005) compared to the CC genotype. This association was not observed after one year of active treatment (p=0.38) (Table 1 ). The common H2 haplotype, characterized by the T allele of rs1205, was associated with a 26% reduction in CRP at baseline (p=0.04), but no effect was observed at year 1 (p=0.47) (Table 2 ). No other SNP or haplotype were associated with CRP at baseline or year 1 (p≥0.09). We observed no associations between SNPs or haplotypes and DAS28 scores at baseline or year 1 (p≥0.10) Conclusions: This study shows that DAS28 can be used for clinical decision-making without adjustment for CRP gene variants, as CRP genotypes and haplotypes were only marginally associated with CRP levels and without any association to the DAS28 score. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1357